Politics applications in the novel Noticia de un secuestro by Gabriel García Márquez - Lebethe, Ketty Hassell; Toloza, Mónica Patricia; Villarreal, Neyla Johanna (Rastros Rostros, 2011)
This article is based on research into “Political proposals in the Colombian novel of the twentieth century”of Universidad Cooperativa de Colombia, Bucaramanga, 2009, this research began in the second semester of 2009 and it ended in the first semester of 2011. Specifically we work on the novel Noticia de un secuestro by Gabriel Garcia Márquez,- a Colombian writer who was born in the Caribbean region in the municipality of Aracataca (Magdalena) March 6th, 1927. This work shows the problem of the twentieth century Colombian politics and a series of kidnappings caused by so-called “extraditable” to avoid extradition.